Infinitesimal rigidity of frameworks / Daud Mohamad - Mohamad, Daud (Universiti Teknologi MARA, Pahang, 1990)
This paper is a continuation of my first article in Gading Jilid 1, Bil 3. So the terms used in this paper should be the same as the first one unless stated. When one considers rigidity of frameworks he/she cannot avoid talking about infinitesimal rigidity. This is because they are inter relating to each other. Infinitesimal rigidity arises from one's ability to avoid infinitesimal motion, in other words, there are no external or internal forces which cannot be resolved reacted on the frameworks. This matter is very useful, especially to engineers and also interesting in the sense that it can be applied to models so that we can see its practicality. This paper will focus on the importance of infinitesimal rigidity in determining the rigidity of framework as a whole.